Exploring Mobility of The Elderly in Urban Public Spaces and Transportation Facilities - Jailani, Sri Fatiany Abdul Kader; Omar, Emi Normalina; Yunus, Noor’ain Mohamad; Maon, Siti Noorsuriani; Hassan, Naffisah Binti Mohd (Advances in Social Sciences Research Journal, 2023)
Ageing is a global issue. As cities grow, the share of residents aged 60 and over also increases. In Malaysia, the population aged 65 years and over increased from 6.5% in 2018 to 6.7% in 2019. Therefore, Malaysia is estimated to reach an ageing nation status in 10 years, and 15% of the population will be at least 60 years old. The World Bank predicts Malaysia will become a "super-aged society" as 20% of the population will be over 65 by 2056. Aligned with the 12th Malaysian Plan (2021-2025), Malaysia has made preparations for the Smart City Initiative, with a primary focus on improving the well-being of its people. In addition, an Intelligent Transport System Blueprint (2017–2022) has been introduced as part of the government's efforts to upgrade the current transportation system. Today's world shows the rise of an ageing population, which has implications in many areas and facilities, such as healthcare, financial services, city planning, transportation, and religious centres. This rising elderly population requires changes in their living environment to make their lives easier. There will be serious problems and challenges in the mobility of the elderly in health service needs and physical areas. Therefore, the primary objective of this conceptual study is to explore the contributing aspects that allow older people with smart mobility to use public spaces and transportation facilities. A qualitative research design is employed to achieve research objectives. This study is helpful for the development of smart cities and transportation planning to support the sustainable mobility of the elderly in Malaysia, which is facing an increasingly ageing society. Also, the study will address the ageing society in the national development plans and revisit existing planning together with physical areas of development to fulfill the needs of the elderly. It is aligned with the National Sustainable Development Goals (SDGs) of increasing the elderly population's quality of life.